IMPLEMENTASI UU NOMOR 11 TAHUN 2010 TENTANG CAGAR BUDAYA DALAM PENGEMBANGAN PARIWISATA BUDAYA DI CANDI TEBING JEHEM, BANGLI - Hamdan Kamal Nugraha; Ariyasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The Jehem Cliff Temple and the Additional Cliff Temple are located in one village, namely Jehem village, Tembuku sub-district, Bangli district, which is a historical heritage in the form of a temple carved on a cliff. Currently the two cliff temples have been protected by the Cultural Conservation Law and their existence must be maintained and utilized as well as possible for the benefit of education, research, tourism and the community's economy. The method used in this article is a field study and literature, by visiting the Jehem Cliff Temple and reviewing books, similar scientific articles, and references related to cliff temples and the use of cultural heritage as a cultural tourism destination. More vigorous promotion through various media should be carried out to attract public interest to visit Tebing Jehem Temple, either to enjoy the nature around the temple, explore the history of the temple, or educational, spiritual activities, in accordance with the mandate of the Cultural Conservation Law in utilizing the potential of cultural heritage. The potential of the surrounding community also supports Jehem Cliff Temple as a cultural tourism because the community produces sokasi crafts from woven bamboo as superior products when visiting the temple. Tri Hita Karana's philosophy, namely the existence of a temple as a historical center, the existence of an area that is still beautiful and supported by the potential of the community in making crafts, supporting the preservation and utilization of cultural heritage.